2003
DOI: 10.1046/j.1540-8175.2003.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Transesophageal Echocardiographic Demonstration of Anatomical Defects in AV Septal Defect Patients Presenting for Reoperation

Abstract: We present two- and three-dimensional transesophageal echocardiographic findings of two adult patients who presented for reoperation after previous repair of a partial atrioventricular (AV) septal defect. Both patients had a cleft in the left AV valve with severe regurgitation. One patient had an additional 10 x 5 mm defect connecting the left ventricle to the right atrium through the AV junction. Three-dimensional echocardiography was superior to two-dimensional echocardiography in comprehensively delineating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Despite this, several studies have demonstrated marked clarity in image rendering using this technique 16–18 . Specifically, superiority to 2D transthoracic echocardiography has been demonstrated in the preoperative assessment of atrioventricular canal defects 19–21 …”
Section: Discussionmentioning
confidence: 99%
“…Despite this, several studies have demonstrated marked clarity in image rendering using this technique 16–18 . Specifically, superiority to 2D transthoracic echocardiography has been demonstrated in the preoperative assessment of atrioventricular canal defects 19–21 …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Specifically, superiority to 2D transthoracic echocardiography has been demonstrated in the preoperative assessment of atrioventricular canal defects. [19][20][21] In addition to diagnostic utility, this technique has shown some promise in assisting surgical and interventional procedures. The use of epicardial 3DE via a rotational transducer and volume mode imaging has been demonstrated in assisting in the surgical closure of atrial septal defects off cardiopulmonary bypass in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional echocardiography has proven useful for the guidance of interventional and surgical procedures. Imaging of the interatrial septum during closure of atrial septal defects was reported by Miller et al (28) and Acar et al (29) and appeared preferable to transesophageal echocardiography guidance. Suematsu et al (30) used three-dimensional echocardiography to monitor robotic atrial septal defect closure in experimental models and reported excellent correlation with directly measured defect size.…”
Section: Validation Of New Technologymentioning
confidence: 99%